LITERARY ANTHROPOLOGY IN THE NOVEL PEREMPUAN BERSAMPUR MERAH BY INTAN ANDARU - Hetilaniar; Anggeraini, Melati; Puspita, Yenny (Universitas PGRI Palembang, 2022)
Therefore, the difficulty that often arises in analyzing novels is having to read repeatedly in order to find concrete data. Therefore, the problem in this study is how the literary anthropology in the novel Perempuan Bersampur Merah by Intan Andaru. The purpose of this research is to identify and analyze literary anhtropology in novel Perempuan Bersampur Merah by Intan Andaru..